Research on the Ripple Current of Support Capacitor for DC Bus - YING Ting; ZHANG Yu; WANG Jian; LIANG Zhiwei (Kongzhi Yu Xinxi Jishu)
Ripple current of support capacitor for DC bus in converter is one of the key factors affecting lifetime of the converters. In industrial processes, in order to save energy, expand capacity, optimize design, multi-motors sharing one DC bus structure is usually used. It analyzed the formation mechanism of ideal ripple current of inverter DC bus, studied the impact of common DC bus resonance on ripple current of capacitor and proposed a method of suppressing ripple current. Simulation results verify the correctness of the method.